Pelatihan Komunikasi Positif dan Penguatan Kepercayaan Diri bagi Siswa Sekolah Dasar di SDN Antasan Besar 7 Banjarmasin - Ratih Pranawa Widagda; Rizky Nazzara; Sabrina Tsalsadifa; Triana Ayu Wulandari; Zuliana Agustin; Sudirwo Sudirwo; Anna Nur Faidah (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to improve positive communication skills and foster self-confidence in students at Antasan Besar 7 Elementary School, Banjarmasin. The background to this activity is the results of observations showing that some students still have low communication skills and lack of self-confidence, characterized by shyness, nervousness, and reluctance to speak in public. The training was conducted by students of Lambung Mangkurat University on September 17, 2025, involving 16 fifth-grade students. The implementation method included preparation, interactive training, role-playing, speaking simulations in front of the class, and evaluation through pre-post observation and questionnaires. The training materials included understanding positive communication, the use of polite language, emotional control, eye contact, and facial expressions, as well as self-confidence-building exercises through the activities